Double Russian Lexical Сopies in the Mari Lexicon - Agyagási, Klára (Slavica, 2018)
The author aims to reconstruct the phonetic, morphological, semantic and chronological peculiarities of three pairs of Mari words (wočko and pečke ‘barrel’, kaďilä and ká·δәn ‘censer’, moľo and mŭľo ‘young fish’) borrowed from Russian dialects. She comes to the conclusion that they can compose pairs as direct and indirect borrowings, different derivational varieties of the same verbal stem or the phonetically resembling Mari representations of two etymologically different Russian dialectal words.